Drawing technique in understanding the meaning of adolescent pregnancy (Research, Society and Development, 2021)
Objective: to investigate the meanings of adolescents about pregnancy. Method: qualitative study of ethnographic aspect, performed with eight pregnant teenagers. The data collection technique was the narrative interview, which was subjected to thematic analysis, and drawing as a complementary technique. The study was initiated after approval by the Ethics Committee with CAAE number 00554512.0.0000.5346. Results: the use of the drawing produced meanings of the bodily changes, which were of reflection about their silhouette, timidity in representing themselves in a drawing and satisfaction with the corporal alterations caused by the pregnancy. In the representations, they were alone, only one included the partner. Conclusion: the drawing allows a more communicative and participatory position during the interviews. Thereby, it recognizes the relevance of using this technique in data collection work with anthropological approach.